RELATIONSHIP OF PERSONAL HYGIENE AND ENVIRONMENTAL SANITATION WITH ENTEROBIASIS IN ORPHANES TODDLER ADHSA SUKOHARJO - Rahmat Budi Nugroho (Jurnal Labora Medika, 2023)
Enterobiasis is a disease caused by infection with the worm Enterobius vermicularis. Pesantren is a place for people who live in the same environment so that it can allow personal hygiene and environmental sanitation is not good. The purpose of this study was to determine whether there was a relationship between personal hygiene and environmental sanitation with enterobiasis in ADHSA Sukoharjo Orphans and to determine  the  percentage  of  enterobiasis  in  children  at  ADHSA  Sukoharjo Orphans Islamic Boarding School. This study used an observational research design. Sampling technique Total Sampling. The source of the data obtained in this study is primary data obtained  from  three  periodic  sampling  carried  out at  the  AHDSA  Toddler  Orphans Islamic Boarding School Sukoharjo in April 2022. The population of this study was 35 people and the sample size was 35 people. Data were analyzed by Chi Square test. The results of the study showed that there were 5.7% (2 respondents) who were infected with Enterobius vermicularis worms from 35 students who were examined. There is a significant relationship between personal hygiene and environmental sanitation with enterobiasis and the percentage of enterobiasis in orphaned Islamic boarding schools children under AdhSA Sukoharjo is 5.7% (2 respondents). Keywords: personal hygiene, environmental sanitation, enterobiasis.